Monitoring of the atmospheric ozone layer and natural ultraviolet radiation. Annual Report 2019. - Svendby, Tove Marit; Hansen, Georg Heinrich; Bäcklund, Are; Nilsen, Anne-Cathrine (NILU, 2020)
This report summarizes the results from the Norwegian monitoring programme on stratospheric ozone and UV radiation measurements. The ozone layer has been measured at three locations since 1979: In Oslo/Kjeller, Tromsø/Andøya and Ny-Ålesund. The UV measurements started in 1995. The results show that there was a significant decrease in stratospheric ozone above Norway between 1979 and 1997. After that, the ozone layer stabilized at a level ~2% below pre-1980 level. 2019 was characterized by low ozone values in April and an “ozone hole” in Southern Norway in December 2019. Denne rapporten presenterer resultatene fra det norske måleprogrammet for totalozon og UV-stråling. Ozonlaget har blitt målt ved tre stasjoner siden 1979: i Oslo/Kjeller, Tromsø/Andøya og Ny-Ålesund. UV-målinger startet i 1995. Resultatene viser at det var en signifikant ozonreduksjon over Norge i perioden 1979 til 1997. Deretter stanset reduksjonen og ozonverdiene stabiliserte seg på et nivå ~2% lavere enn verdiene før 1980. Mest karakteristisk for 2019 var et tynt ozonlag i april 2019 og et «ozonhull» over Sør-Norge i desember 2019. publishedVersion